Application of a Collaborative Learning Model to Improve Writing Skills of Class V SD UPT SPF Students at Tuntungan Pancur Batu School Year 2023-2024 - Rahmawati, Rahmawati; Sutikno, Sutikno (PT Inovasi Pratama Internasional, 2024)
Through writing activities, a person can express thoughts and ideas to achieve goals and objectives. The objectives of this research are: (1). To describe the process of developing a collaborative learning model in improving students' writing skills and describe the effectiveness of using a collaborative learning model in improving the writing skills of fifth-grade students UPT SPF Elementary School Number 101826 Tuntungan Pancur Batu. The research design in this research is research and development. The subjects of this research were fifth-grade students at UPT SPF No. Elementary School. 101826 Tuntungan Pancur Batu for the 2023-2024 academic year. The object of research for this research is the writing learning model, namely a collaborative learning model implemented in class V students. The results of the research were: (1). The process of developing a collaborative learning model in improving descriptive text writing skills for fifth-grade students at UPT SPF Elementary School Number 101826 Tuntungan Pancur Batu, namely 1) orienting students, 2) forming groups, 3) preparing learning tasks, 4) facilitating student collaboration and 5) providing value and evaluate collaborative learning. (2). The validation results show that in the feasibility aspect of the material, an average validation score of 4.19 was obtained in the good category, then in the aspect of feasibility of presenting the material, an average validation score of 4 was obtained in the good category and the aspect of language appropriateness, the average score was found. -The validation average is 4.2 in the good category. (3) The collaborative learning model is effective in improving descriptive text writing skills by fifth-grade students at SD UPT SPF Number 101826 Tuntungan Pancur Batu.